The effect of changes in tax-benefit policies on the income distribution in 2008-2015 - Paola De Agostini; Alari Paulus; Iva Tasseva (University of Essex, Institute for Social and Economic Research (ISER), 2016)
We apply microsimulation techniques to estimate the first-order effects of tax-benefit policy changes since the beginning of the financial and economic crisis in 2008. Using the EU tax-benefit model EUROMOD in combination with the EU-SILC 2012 micro-data, we provide comparative estimates for EU-27 in 2008-2014 as well as for 21 EU member states in 2014-2015. The analysis covers direct tax and cash benefit changes and evaluates their effects on the income distribution, poverty and inequality levels, holding population characteristics and market incomes constant, thereby, isolating direct policy effects from other factors shaping the income distribution. Two different indexation approaches are used to adjust benchmark policies over time - prices and market incomes - and explore the sensitivity of results. We find substantial cross-national variation throughout the whole period. At the EU level, policy changes in the first half of the period (2008-2011) were poverty-reducing and had a positive effect on mean incomes, while the effects were the opposite in the later period (2011-2014); and inequality-reducing in both periods.
Keywords: D31; H23; I38; 330; Income distribution; tax-benefit policies; European Union